2016
DOI: 10.1007/s10517-016-3321-6
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Toxicity of Silver Nanoparticles in HepaRG Cell Spheroids

Abstract: We studied the effects of silver nanoparticles (10 nm) on HepaRG cell spheroids simulating liver tissue. The mathematical model was proposed that describes nanoparticle diffusion in a spheroid consisting of 5000 cells depending on the external nanoparticle concentration. It was demonstrated that cells in the 3D model were less sensitive to the toxic effects of nanoparticles in comparison with 2D cultures. Impaired integrity of the cell membrane did not deteriorate cell viability (according to MTT test).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Cells in a 3D system tolerate higher silver concentrations than in a 2D system, which further supports the probability of success of such a material as coating for prosthetic joints. 65,66 In an in vivo setting rather than in cell cultures, the therapeutic window may therefore be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Cells in a 3D system tolerate higher silver concentrations than in a 2D system, which further supports the probability of success of such a material as coating for prosthetic joints. 65,66 In an in vivo setting rather than in cell cultures, the therapeutic window may therefore be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, ROS production following minimal cellular insult induces mast cell activation. Silver NPs can either damage cell membranes or enter cells by diffusion for some cell types, including endothelial cells or hepatocytes, and by endocytosis in phagocytic cells . The K + efflux followed by membrane damage may trigger histamine release from mast cells directly or indirectly via the production of intracellular ROS .…”
Section: Resultsmentioning
confidence: 99%
“…Although many in vitro studies focusing on NP-induced toxicity used 2D cultivated cells, recently 3D microtissues have been used in this context. 37,39,67 Nanosilica have been described to induce cellular oxidative stress and to cause inflammation and DNA damage leading to cell death in various 2D cell types. 68,69 Landgraf et al reported only weak biological effects of SiO 2 NPs on HepG2 cells.…”
Section: Cytotoxicity Of Sio 2 Nps In 3d Liver Microtissuesmentioning
confidence: 99%
“…32,35 In recent years, liver microtissues were used as a model for NP toxicity assessment. 34,[36][37][38][39] Dubiak-Szepietowska et al observed a stronger cytotoxic effect of Ag, ZnO, and SiO 2 NPs on HepG2 cells when grown in 2D compared to cells grown in 3D hydrogels. 34 The lower sensitivity to toxic concentrations of Ag NPs was also detected in HepaRG cell spheroids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation